The role of environmental justice reform in corporate green transformation: Evidence from the establishment of China’s environmental courts - Tao, Shuang; Hai, Mengdie; Fang, Ziwei; Zheng, Dechang (Frontiers in Environmental Science, 2023)
Using China’s establishment of environmental courts as a quasi-natural experiment, this paper adopts a difference-in-difference (DID) method to investigate how this environmental justice reform can influence corporate green transformation from the perspective of green technology innovation. Our empirical findings demonstrate that the establishment of environmental courts significantly enhances green technology innovation among enterprises. The more effective judicial enforcement and better public awareness of the environment brought by the environmental courts will increase the cost of illegality and external supervision pressure for firms, which will lead firms to innovate in green technology. Furthermore, the positive and significant effect of environmental courts on green technology innovation is more pronounced in state-owned enterprises (SOEs) and enterprises located in regions where local protectionism is more serious. At the same time, in regions with a more ideal environmental legal system, environmental courts have more significant promoting effects on green technology innovation.